Magyary Zoltán miniszteri tanácsos átirata a m. kir. Tisza istván Tudományegyetem részére a főiskolai hallgatókra vonatkozó statisztikai adatgyűjtés új rendszeréről (1929. december 27.) - Király, Sándor (Gerundium, 2017)
The Official Communication of Ministerial Counsellor Zoltán Magyary to the István Tisza University about the New System of the Collection of the Students’ Statistical Datas. In the autumn of 1929 Zoltán Magyary finished his famous memorandum to the Minister of Religion and Education Kuno Klebelsberg about the social care of the students of the universities. In this work Zoltán Magyary was urging to make a detailed statistical survey about the students of the universities in order to the government could take steps to solve their social problems. After this he began to work out those special questions which can gave the most important informations to the government. In the end of December in 1929 Magyary sent his official communication to the universities about the new system of statistical datas’ collection. The István Tisza University got very important instructions about the new way of the process of the collection. And this statistical survey was the basis of the famous statistical analysis of Laky Dezső (1930) which was the first detailed work about this. Magyary’s official communication is a very important historical source because this statistical collection system was being used to the end of this period. The evidence of it is the other published source, the official communication of József Asztalos which was sent to the university in 1939.